PECULIARITIES OF THE LANGUAGE OF CRIMEAN BULGARIANS (BASED ON THE POPULATION CENSUS AND INTERVIEWS OF NATIVE BULGARIAN SPEAKERS IN CRIMEA) - Andryushchenko; Berezina; Skurikhina (Revista Inclusiones, 2020)
The problem of preserving the native languages of small peoples in a multicultural region remains a live issue today. The fundamental theoretical basis for solving this problem is the study of linguistic consciousness. It is especially significant when referring to fixing and analyzing the language consciousness of “outgoing” communities. Crimean Bulgarians can be considered such a group. Studying their linguistic consciousness, analyzing features of their linguistic competence today is extremely difficult, since the number of native speakers of the Bulgarian language in Crimea is extremely small, and most native speakers are mostly elderly people.